Визначення робочої температури композитних елементів рухомих з’єднань в зоні тертя - Аулін, В. В.; Деркач, О. Д.; Гриньків, А. В.; Макарнеко, Д. О.; Aulin, V.; Derkach, O.; Hrynkiv, A.; Makarenko, D.; Аулин, В. В.; Деркач, А. Д.; Гринкькив, А. В.; Макаренко, Д. А. (ТДАТУ, 2021)
В статті сформульовано проблеми, пов’язані з розподіленням теплового потоку у трибоспряженнях сільськогосподарської техніки. Наведено основні напрямки впровадження полімерно-композитних матеріалів в конструкції машин і механізмів. Розглянуто протікання явища теплопровідності в полімерному підшипнику, що обертається на валу або в корпусі. Наведено рівняння для визначення розподілення теплоти у вигляді теплового потоку та вираз для визначення теплового потоку, що надходить у зовнішнє середовище через підшипник і вал. Результати випробувань експериментального підшипника підтвердили працездатність запропонованого типу рухомих спряжень «полімерний композит-сталь». Запропоновані рівняння для визначення температури в зоні тертя при взаємодії полімерно-композитних матеріалів зі сталлю дозволяють обґрунтувати допуски та посадки вказаних елементів рухомих з’єднань. The article formulates the problems associated with increasing the durability of agricultural machinery. It is proposed to implement in mobile joints tribo-mated parts type "polymer composite-steel". The main directions of introduction of polymercomposite materials in the design of machines and mechanisms are given. The course of the phenomenon of thermal conductivity in a polymer bearing rotating on a shaft or in a housing is considered. The equation for determining the heat distribution in the form of heat flux is given. The equation for determining the heat flux entering the environment through the bearing and shaft is proposed. It is assumed that the temperature of the housing at each point is constant and coincides with the temperature of the outer surface of the bearing. Determination of the temperature field in the polymer bearing allows to calculate the change in its outer and inner diameter, ie to provide temperature compensation at optimal values of clearance and tension in the connections "shaft - liner" or "liner - housing". It was found that the highest temperature in the friction zone was 86 ° C (runningin process). The average temperature zone the friction was in the range of 48-52 ° C. Estimated values of temperature in accordance with the above equations - 56 ° C. It was found that the temperature does not increase depending on the work time of the bearing. Changes in the physical and mechanical properties of the bearing material not detected. No changes in the geometrical parameters of the experimental parts were detected. At forced introduction of natural abrasive in a friction zone the character of friction didn't change. The results of research of the experimental bearing indicate the feasibility of using tribo-mated parts typеs "polymer composite-steel" in the constructions of machines and mechanisms. The proposed equations for determining the temperature in the friction zone during the interaction of PCM with steel allow to substantiate the tolerances and landings of the elements of mobile joints made of PCM. В статье сформулированы проблемы, связанные с повышением долговечности сельскохозяйственной техники. Приведены основные направления внедрения полимерно-композиционных материалов в конструкции машин и механизмов. Приведены уравнения для определения распределения теплоты в виде теплового потока и выражение для определения теплового потока, поступающего во внешнюю среду через подшипник и вал. Результаты испытаний экспериментального подшипника подтвердили работоспособность предложенного типа подвижных сопряжений «полимерный композит-сталь». Предложенные уравнения для определения температуры в зоне трения при взаимодействии полимерно-композитных материалов со сталью позволяют обосновать допуски и посадки указанных элементов подвижных соединений.
Determination of the operating temperature of composite elements of movable joints in the friction zone
Определение рабочей температуры композитных элементов подвижных соединений в зоне трения
Keywords: рухомі з’єднання; температура; полімерно- композитні матеріали; трибоспряження; полімерний композит-сталь; movable joints; temperature; polymer-composite materials; tribo-mated parts; polymer composite-steel; подвижные соединения; температура; полимерно- композиционные материалы; трибосопряженные детали; полимерный композит- сталь